Optogenetic methods and technologies in solving applied medical problems - L. E. Sorokina; V. I. Petrenko; M. V. Subbotkin; A. A. Kulanova; A. S. Kucherenko; A. V. Kubyshkin; I. I. Fomochkina; A. Yu. Nomerovskaya; S. I. Halilov (Бюллетень сибирской медицины)
Optogenetics is an innovative and fast-growing field of science combining the advances in molecular biology and laser technologies to monitor various biochemical processes in the cell and to control its activity using light. Therefore, this review is devoted to the implementation of the optogenetic approach to diagnosis and treatment of various socially sensitive diseases at the molecular and genetic level. Furthermore, the article considers different methods of delivery and incorporation of genetic constructs encoding transmembrane proteins. New fiber optic technologies used to develop implantable devices for generating and recording signals in excitable tissues are described. Besides, the most state-of-the-art and popular registration methods are considered in the review.